Multidrug-resistant Acinetobacter Baumannii Ventilator- Associated Pneumonia at Paholpolpayuhasena Hospital - Pintong, Thaned (Journal of Health Science of Thailand, 2018)
The objective of this retrospective study at Internal Medicine Department of Paholpolpayuhasena Hospital, from January 1 to December 31, 2007, was to determine clinical characteristic, risk factors, susceptibility test for antimicrobial agents, result of treatment and adverse reactions of antimicrobial agents of multidrug-resistant Acinetobacter baumanniiventilator-associated pneumonia. The total number of patients were 30, mean age was 69 years old, had co-morbidities 87 percent. There were early-onset VAP 10 percent, late-onset of VAP Ventilator- Associated Pneumonia 90 percent of which, 30 percent were treated by colistin, 70 percent were treated by other antimicrobial agents, total mortality rate was 63 percent, mortality rate of colistin group and non-colistin group was 44 percent and 71 percent respectively there was no statistical significant among them, rate of acute renal failure of colistin group and non-colistin group was 44 percent and 9.5 percent respectively, which differed with statistical significance (p < 0.05).